Capitalist restructuring and the Pacific Rim - Palat, Ravi Arvind (RoutledgeCurzon studies in the modern history of Asia, 2004)
This book situates the evolution of the high growth economies along Asia's Pacific Rim after the Second World War within broader global political and economic changes.